Construction of Outcome Functions Guaranteeing Existence and Pareto Optimality of Nash Equilibria - Hurwicz, Leonid; Schmeidler, David (Econometrica, 1978)
Recent formulations of social decisions problems focus on rules by which a group of individuals (the society) arrives at a choice among available alternatives. Such a rule, which we shall call the outcome function (Gibbard's "game form, " see [ 3 J), specifies the